The brilliant world of Tom Gates - Pichon, Liz, ....- (Massachusetts : Candlewick Press, 2015)
I'm Tom Gates. When my teachers don't have their beady eyes on me, I like to draw pictures and think of ways to annoy my grumpy sister, Delia. My teachers think I am easily distracted and "lack focus", which is a bit harsh, because right now I am very focused on which cookie I should eat first. Mmmm?
Keywords: Avontuur; Graphic novel